Model Simultanitas Dividend Payout Ratio, Trading Volume Activity Dan Laju Inflasi Terhadap Volatilitas Saham Pada Perusahaan LQ45 Periode 2016-2020 - Yeni Ariesa; Fredy Fredy; Sendy Amadha (Management Studies and Entrepreneurship Journal (MSEJ), 2022)
The reason of this inquire about is to discover out and analyze the show of synchronization of profit payout proportion, changing volume movement and swelling rate on stock instability in LQ45 companies for the 2016-2020 period. Stock price volatility is important and interesting to study because in today's era people are more interested in investing in the capital market because it promises to be in the future. So that by examining the volatility of stock prices, investors know better what factors can affect the difference in fluctuations in stock prices. By examining what factors affect the volatility of stock prices, investors can calculate the risks that will be faced later. The population in this consider includes a period of LQ45 companies as numerous as 45 companies and the ppsample with a add up to of 225 units of examination. The inquire about strategy applies to numerous direct relapse investigation methods. The comes about of this think about are the Profit Payout Proportion, Exchanging Volume Action and Expansion at the same time and in part have no impact on stock instability. Keywords : Dividend Payout Ratio, Trading Volume Activity, Inflation Rate, Stock Volatility.